FOCUS GROUP DISCUSSION UNTUK MEMBANGUN MODEL KEGIATAN TANGGUNG JAWAB SOSIAL LINGKUNGAN - Roostika, Ratna; Susilowati, Christin; Muafi, ' (PEDULI: Jurnal Ilmiah Pengabdian Pada Masyarakat, 2018)
The implementation of Corporate Social Responsibility  (CSR) by corporations operating  in Indonesia  has  nowadays  becoming  an  obligator y.  CSR  has  been  defined  as  activities representing compan y’s corporate social responsibility and environment. Both private and public companies should allocate  their  budget  to  CSR activities.  When implementing different kinds of  CSR programs, many companies have encountered problems concerning what kinds of program that match with the needs of the societies  and  environment  surround  the  company’s location.  In  particular,  there have been questions about finding the kind of CSR programs that match with compan y’s vision -mission as well as strategic directions. This community service program was conducted to assist the company in building a CSR model specific  to  company  characteristics  as  well  as  finding  priority  identifications  program  relating  to company’s CSR (social and environment responsibility). The program is conducted in one of Government (BUMN) company in the food sector. The method practiced for this community service is socialization on CSR program, Focus Group Discussion (FGD) and questionnaire distribution for building CSR model and CSR  program identifications. Finding have  identified  some  main  areas  of priority program such  as: education  and  training,  health  improvement, infrastructure and  facility upgrading, supporting worship facilities,  technology assistance,  building  human  resource  talents,  managing natural  environment and minimizing potential risk of natural disaster.